EVIDÊNCIA DE HEMORRAGIA PULMONAR INDUZIDA PELO EXERCÍCIO EM CAVALOS DE SALTO DE 1,00 M – 1,20 M - Muller da Silva, Mariana; Dufour Eisenback, Yolanda; Medeiros Novicky Durães, Evelyn; Ribeiro da Silva, Karla; Coelho Bastos, Luis Fernando; Michelotto Júnior, Pedro Vicente (Archives of Veterinary Science, 2013)